Induksi Kalus Gaharu dengan NAA dan BAP Secara In Vitro - Amalina Wahyuni; Benni Satria; Aprizal Zainal (Universitas Sebelas Maret, 2020)
Agarwood has a high economic value because they have many benefits that cause agarwood to be hunted to meet the increasing market demand and its presence in nature is decreasing due to unwise conventional retrieval systems.The research objectives were to study the effect and determine the best concentration of NAA and BAP in callus induction of agarwood (Aquilaria malaccensis Lamk.). This research was conducted in the Tissue Culture Laboratory, Faculty of Agriculture, Andalas University from October 2018 until January 2019. The leaves of Agarwood were used as explants. The method used was completely randomized design (CRD) with different combinations of NAA and BAP (1.5 + 0.5 ppm, 3.0 + 0.5 ppm, 1.5 + 1.0 ppm, and 3.0 + 1.0 ppm). Data were analyzed using the F test and continued with Duncan’s Multiple Range Test at a level of 5%. The results showed that there was the effects of combination of growth regulator substances NAA and BAP on callus induction of agarwood. The concentration of NAA 3.0 ppm + BAP 0.5 ppm was the best in inducing callus with the percentage of explants life and explants form callus with 100%. The color of callus obtained varies, yellow, brownish yellow and brown. All structures callus gained in this research was compact. Yellow callus and compact structure could be utilized for organogenesis.